Identifikasi Kelimpahan, Bentuk, Warna, Ukuran Mikroplastik dan Pollution Load Index di Sungai Kalanganyar Sedati Kabupaten Sidoarjo - Devi Mutiara Salsabila; Diah Karunia Binawati (Universitas PGRI Adi Buana Surabaya, 2026)
Microplastics are plastic particles smaller than 5 mm in diameter that negatively impact aquatic environments and human health. This study aims to identify the abundance, shape, color, and size of microplastics in the Kalanganyar River, Sedati, Sidoarjo Regency, as well as to assess pollution levels using the Pollution Load Index (PLI). Samples were collected from six sites along the river using purposive sampling and analyzed microscopically at the Ecoton Laboratory in Gresik. The results showed an average microplastic abundance of 2,000 particles/m³ of water, with the highest concentration at Dam Gisik (2,900 particles/m³) and the lowest near residential and fishing areas (1,400 particles/m³). Microplastics were dominated by fibers (59%), followed by films (30%) and fragments (11%), with transparent as the most common color (32%). The most dominant microplastic size range was 0.5–1 mm (35%). The average PLI value of 625.47 classified the pollution as high (class IV), indicating a serious ecological risk. Human activities such as washing, fishing, and waste disposal contribute significantly to microplastic accumulation in this aquatic environment. Keyword : Identification microplastic, water of the Kalanganyar River, Sedati, Pollution Load Index